The benefits of advanced data analytics in basketball: approach of managers and coaches of Lithuanian basketball league teams - Demenius, J.; Kreivyte, R. (Baltic Journal of Sport and Health Sciences, 2017)
Background. Many industries use a variety of statistical models for a decision-making, but no industry relies on analytical data as a professional sport (Davenport, 2014). Sports organization management and decision-making have a direct relationship with the sports teams and this relationship is called a comprehensive statistical analysis (Radovanovi., Radoji.i., Jeremi. & Savi., 2013). Alamar (2013) argues that a detailed statistical analysis of the game activities is an important aspect in order to more accurately assess the player's market value. Methods. The sample consisted of 30 respondents (10 managers, 10 coaches, 10 coach assistants) of the 10 men's basketball teams. Managers and coaches of Lithuanian Basketball League teams had to fill in online questionnaire, the main focus of which was to identify their opinion about advanced data analytics. The questionnaire was designed based on scientific studies (Alamar, 2013; Martinez & Martinez, 2011). Questionnaire scales were tested using SPSS 20.0 statistical analysis program. Results. Statistical analysis showed that questionnaire reliability was average (Cronbach alpha = .549..558). The survey results showed that the teams of Lithuanian Basketball League there employ professionals whose main goal is to analyse performance indicators, statistical data of opponents and new incoming players. Majority of managers and coaches believe that new information technologies of advanced basketball data could help improve team performance results and draw more attention to basketball from fans' perspective. It was found that managers ad coaches thought that offensive strategy depends on the players of the team. Coaches and managers had a positive approach to basketball analytics and believed that it had a bright future in basketball industry. Conclusions. The correct use of limitless data would definitely help improve team performance and effectively use their financial resources recruiting the most efficient players. (Abstract)